2017
DOI: 10.17705/1thci.00096
|View full text |Cite
|
Sign up to set email alerts
|

E-mentoring: A Model and Review of the Literature

Abstract: Abstract:With the growth of technology and greater use of virtual teams, organizations have increasingly begun to use ementoring for socializing, training, and developing individual employees via technology. Despite the growing importance of e-mentoring, relatively little research has examined its process or effectiveness. Therefore, we: 1) provide a framework for understanding the e-mentoring process, 2) review the e-mentoring literature, and 3) present hypotheses to generate additional research on e-mentorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
14

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 127 publications
0
23
0
14
Order By: Relevance
“…Research remains limited on which theoretical approaches are most effective for online mentoring in distance education. Differences in online-only and blended mentoring programs will impact the theoretical approach used (Neely, Cotton, & Neely, 2017). Research has shown that traditional frameworks can be adapted for online use.…”
Section: Theoretical Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research remains limited on which theoretical approaches are most effective for online mentoring in distance education. Differences in online-only and blended mentoring programs will impact the theoretical approach used (Neely, Cotton, & Neely, 2017). Research has shown that traditional frameworks can be adapted for online use.…”
Section: Theoretical Approachesmentioning
confidence: 99%
“…Mentors need to learn how to mentor effectively or have mentoring skills reinforced through training. Training is often cited as an important requirement for effective mentoring, but the characteristics of those trainings are often vague (Anderson, Motto, & Bourdeaux, 2014;Neely et al, 2017). In a review of mentoring programs, Ehrich, Hansford, and Tennent (2004) explained, "Administrators must .…”
Section: Developing Effective Mentorsmentioning
confidence: 99%
“…Beyond face-to-face mentorship, prior research demonstrates the efficacy and challenges of e-mentoring (use of social computing technologies, such as video-conference, email, online networking sites) as the primary connection between a mentor and protégé in a dyadic mentorship relationship [37]. Ementoring sidesteps many of the barriers seen in traditional face-to-face mentorship models that may prevent a potential protégé from obtaining and benefiting from a mentor [5,46].…”
Section: Social Computing For Dyadic Mentorshipmentioning
confidence: 99%
“…However, prior research has not investigated how technology might support and expand access to face-to-face mentorship (i.e., sponsorship) in SUD recovery. Further, prior work demonstrates a strong need for understanding privacy, safety, and other social concerns for blended mentorship [37]. We address these challenges by identifying socio-technical opportunities and risks of blended mentorship for SUD recovery.…”
Section: Social Computing For Dyadic Mentorshipmentioning
confidence: 99%
“…La actividad de mentoría ha sido definida como una relación que puede ser formal o semiformal entre una persona senior o mentor, y otra persona con menos experiencia (mentorizado, mentee, o telémaco), con el objetivo final de desarrollar las competencias y capacidades de afrontamiento que el recién llegado adquiriría con más dificultad o más lentamente sin ayuda (Single y Muller, 2001;Neely, Cotton y Neely, 2017). La persona más experimentada trata de guiar a la otra persona con menor experiencia sobre un ámbito concreto en el desarrollo de habilidades, conocimientos y factores psicosociales, a través del establecimiento de una relación de confianza.…”
Section: Introductionunclassified